The COVID-19 in athletes (COVA) study: a national study on cardio-pulmonary involvement of SARS-CoV-2 infection among elite athletes. Issue 1 (31st December 2023) - Rasmusen, Hanne Kruuse; Aarøe, Mikkel; Madsen, Christoffer Valdorff; Gudmundsdottir, Helga Lillian; Mertz, Kenneth Hudlebusch; Mikkelsen, Astrid Duus; Dall, Christian Have; Brushøj, Christoffer; Andersen, Jesper Løvind; Vall-Lamora, Maria Helena Dominguez; Bovin, Ann; Magnusson, S. Peter; et al.
ABSTRACT: Background: COVID-19 can cause cardiopulmonary involvement. Physical activity and cardiac complications can worsen prognosis, while pulmonary complications can reduce performance. Aims: To determine the prevalence and clinical implications of SARS-CoV-2 cardiopulmonary involvement in elite athletes. Methods: An observational study between 1 July 2020 and 30 June 2021 with the assessment of coronary biomarkers, electrocardiogram, echocardiography, Holter-monitoring, spirometry, and chest X-ray in Danish elite athletes showed that PCR-tested positive for SARS-CoV-2. The cohort consisted of male football players screened weekly (cohort I) and elite athletes on an international level only tested if they had symptoms, were near-contact, or participated in international competitions (cohort II). All athletes were categorized into two groups based on symptoms and duration of COVID-19: Group 1 had no cardiopulmonary symptoms and duration ≤7 days, and; Group 2 had cardiopulmonary symptoms or disease duration >7 days. Results: In total 121 athletes who tested positive for SARS-CoV-2 were investigated. Cardiac involvement was identified in 2/121 (2%) and pulmonary involvement in 15/121 (12%) participants. In group 1, 87 (72%), no athletes presented with signs of cardiac involvement, and 8 (7%) were diagnosed with radiological COVID-19-related findings or obstructive lung function. In group 2, 34 (28%), two had myocarditis (6%), and 8 (24%) were diagnosed with radiological COVID-19-related findings or obstructive lung function. Conclusions: These clinically-driven data show no signs of cardiac involvement among athletes who tested positive for SARS-CoV-2 infection without cardiopulmonary symptoms and duration <7 days. Athletes with cardiopulmonary symptoms or prolonged duration of COVID-19 display, exercise-limiting cardiopulmonary involvement.